Typhoons and the Inequalities of Philippine Society and History - Warren, James Francis (Archīum Ateneo, 2016)
Cyclonic storms have helped shape the character of particular regions and areas in the Philippines. But typhoons have not affected all people and all areas in the archipelago equally. Patterns of death and damage from cyclonic storms and the capacity of people to recover and reconstruct their livelihoods reveal differences based on history, regional wealth, and sociopolitical organization. Thisarticle provides comparative examples and explores aspects of the impacts of typhoons—specifically those of 1831, 1882, 1970, 2004, 2006, 2009, and 2013—on Philippine society and history, with particular reference to population increase and cyclonic storms; economic development and typhoons; and political development and typhoons.Keywords: Philipp ine typhoons • population increase • economic development • politics • extreme weather